A Note on Selected Brand Names of E-Cigarettes. (2nd January 2016) - Nuessel, Frank
Abstract : This brief note has a fourfold purpose: (1) to define the concept of "e-cigarette"; (2) to discuss succinctly collateral aspects of e-cigarettes (product development, health and legal features, linguistic dimensions); (3) to explain the notion of brand name; and (4) to review selectively brand names for e-cigarettes in order to determine the marketing strategies employed. Finally, there is an appendix with a corpus of the selected e-cigarette brand names.